HLA B27 allele types in homogeneous groups of juvenile idiopathic arthritis patients in Latvia - Guseinova Dinara; Lazareva Arina; Sochnevs Arturs; Zavadska Dace; Eglite Jelena; Stanevicha Valda; Shantere Ruta; Gardovska Dace (BMC, 2010)
Abstract Juvenile idiopathic arthritis (JIA) is a heterogeneous condition and therapeutic strategies vary in different JIA types. The routinely accepted practice to start with Sulphasalazine (SS) as the first line treatment in patients with HLA B27 positive JIA proves to be ineffective in a large proportion of children. Objective to investigate HLA B27 positive JIA patients clinical characteristics, determined HLA B27 allele types and their connection with antirheumatic treatment in homogenous patient groups. Materials and methods 56 patients diagnosed with JIA and observed over the period 2006 to 2009 included in the study. HLAB27 allele types were determined using PCR method. Results In HLA B27 positive JIA patients mean disease onset was 12.34 ± 3.3 years. Most common (44%) JIA type was enthesitis related arthritis. Positive response to the treatment with SS was found in 32% of patients, Methotrexate (MTX) - in 43%, combined treatment - SS with MTX was effective in 12.5%. 12.5% of patients required combination MTX with Enbrel. Eight HLA B27 allele types were found in JIA patients in Latvia: *2702, *2703, *2704, *2705, *2710, *2715, *2717, *2728. The most common was *2705 - in 55% of cases. Among all the patients enthesitis related arthritis most commonly occurred in patients with HLAB*2705 allele (OR = 2.01, p < 0.02), oligoarthritis in patients with *2710 allele (OR = 3.0, p < 0.04) and polyarthritis with *2717 allele (OR = 3.0, p < 0.05). In patients with *2705 allele effective treatment was MTX (OR = 1.13, p < 0.03) and MTX with SS (OR = 2.02, p < 0.05), but in patients having *2703 allele - MTX with Enbrel (OR = 2.94, p < 0.02). Conclusions There are 8 different HLA B27 alleles in JIA patients in Latvia and the most common is *2705, but in order to assert them to be disease associated alleles, more extensive studies are needed, including control group of HLA B27 positive healthy individuals. Standard treatment approach with SS proves to be unsatisfactory in the majority of JIA patients. To improve children's quality of life achieving rapid disease control, the first line treatment in HLA B27 positive patients should be MTX. In order to start with the most appropriate drug it is necessary to determine HLAB 27 type at the onset of disease.